2019
DOI: 10.29252/jafm.12.05.29842
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Studies of Secondary Injection in Nozzle Divergence for Thrust Augmentation

Abstract: Thrust augmentation in rocket engines using secondary injection in the diverging part of a nozzle is an innovative extension of after burners. This technique finds application in single stage to orbit propulsion devices, where the nozzle has to work at varying ambient pressures. Experimental and numerical studies have been conducted with varying cross flow and injection conditions to analyse the performance augmentation in a 2D nozzle. Schlieren images and wall pressure data are obtained from the experiment. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The secondary injection causes a rise in wall static pressure, which has a positive association with injection pressure When there is a secondary injection, thrust augmentation occurs. In the current research, it has also been proven to be effective in delaying flow separation toward the outlet [35]. The bell outperforms the linear nozzle by just 3%, despite having a 10% bigger subsonic layer at the nozzle output plane than the 30° linear expander [51].…”
Section: …… (1)mentioning
confidence: 78%
See 1 more Smart Citation
“…The secondary injection causes a rise in wall static pressure, which has a positive association with injection pressure When there is a secondary injection, thrust augmentation occurs. In the current research, it has also been proven to be effective in delaying flow separation toward the outlet [35]. The bell outperforms the linear nozzle by just 3%, despite having a 10% bigger subsonic layer at the nozzle output plane than the 30° linear expander [51].…”
Section: …… (1)mentioning
confidence: 78%
“…Pressure oscillations begin to build up over the nozzle wall during the transition phenomena with modifying the Mach number of the injected secondary flow, which may cause significant quantities of unfavorable side loads. [35] Film cooling theory: The investigation of tangential, supersonic film cooling in a nozzle flow under supersonic conditions The following assumptions are also presumed to be true: In terms of temperature, Mach number, and velocity, the coolant, which is gas, differs significantly from the hot gases. Its composition also differs from that of the nozzle hot gas.…”
Section: Thermal Characteristics Of Bell Nozzle In Supersonic Enginementioning
confidence: 99%
“…This is owing to the kinetic energy that affects the total energy enhancement released along the nozzle cavity. The flow reaches a supersonic speed after reaching the throat section, causing the kinetic energy to be higher in the divergent section [58]. Hence, it can be concluded that the most significant convergent angle generates the highest total energy.…”
Section: Resultsmentioning
confidence: 98%
“…A rise in static pressure by the wall of the nozzle because of secondary fuel injection, showing compatibility with fuel injection pressure. It can be seen for sufficient chamber pressure, secondary injection system causes thrust augmentation [3]. Ankit et.al reviewed about pintle injector mentioning about spray patterns and the effect of thrust based on total momentum ratio as well as length to duct ratio.…”
Section: Icdmme-2021mentioning
confidence: 99%